Twenty Years’ Experience in Retroperitoneal Lymph Node Dissection for Testicular Cancer in a Tertiary Referral Center - Angelo Mottaran; Amelio Ercolino; Lorenzo Bianchi; Pietro Piazza; Francesco Manes; Sasan Amirhassankhani; Marco Salvador; Francesco Chessa; Beniamino Corcioni; Alessandro Bertaccini; Riccardo Schiavina; Eugenio Brunocilla (Medicina, 2023)
Background and Objectives: The aim of this article is to present a single-surgeon, open retroperitoneal lymph node dissection (RPLND) series for testicular cancer in a high-volume center. Materials and Methods: We reviewed data from patients who underwent RPLND performed by an experienced surgeon at our institution between 2000 and 2019. We evaluated surgical and perioperative outcomes, complications, Recurrence-Free Survival (RFS), Overall Survival (OS), and Cancer-Specific Survival (CSS). Results: RPLND was performed in primary and secondary settings in 21 (32%) and 44 (68%) patients, respectively. Median operative time was 180 min. Median hospital stay was 6 days. Complications occurred in 23 (35%) patients, with 9 (14%) events reported as Clavien grade ≥ 3. Patients in the primary RPLND group were significantly younger, more likely to have NSGCT, had higher clinical N0 and M0, and had higher nerve-sparing RPLND (all p ≤ 0.04) compared to those in the secondary RPLND group. In the median follow-up of 120 (56–180) months, 10 (15%) patients experienced recurrence. Finally, 20-year OS, CSS, and RFS were 89%, 92%, and 85%, respectively, with no significant difference in survival rates between primary vs. secondary RPLND subgroups (p = 0.64, p = 0.7, and p = 0.31, respectively). Conclusions: Open RPLND performed by an experienced high-volume surgeon achieves excellent oncological and functional outcomes supporting the centralization of these complex procedures.